Petrogenesis of zoned and unzoned mafic pegmatites: An insight from the Palaeoproterozoic mafic-ultramafic Hamn intrusion, Northern Norway - Heckmann, Paul; Palinkaš, Sabina Strmić; Hansen, Harald; Iacono-Marziano, Giada; Rajič, Kristijan; Forien, Mélanie; Bergh, Steffen (Lithos, 2022)
International audience Mafic pegmatites have been reported from various geological environments, including ophiolites, layered magmatic intrusions, and volcanic arcs, but their petrogenesis stayed poorly constrained. This study brings new mineralogical and geochemical data obtained from unzoned and zoned gabbroic pegmatites hosted by the 1.8 Ga mafic-ultramafic Hamn intrusion, Northern Norway, with an aim to improve our understanding of the primary magmatic physicochemical factors that control the development of pegmatitic textures in mafic rocks.The unzoned mafic pegmatites in the Hamn intrusion are hosted in gabbronorite and gabbro. The pegmatites differ macroscopically from the gabbronorite only by grain size and the color of feldspars. The bulk chemical compositions, including REE concentrations and rock-forming mineral assemblages of both rocks, are identical. The mineral composition of the pegmatite and host gabbro overlap. However, the pegmatite experienced epidotization and scapolitization, suggesting that H2O- and chlorine were essential in the formation. Furthermore, the pyroxene of the pegmatite shows a more distinct negative Eu anomaly than the pyroxene of the host gabbronorite. Amphibole dyklets associated with the unzoned pegmatite pockets consist of Cl-rich pargasite and Cl-scapolite, indicating that the fluid pressure during crystallization of the unzoned pegmatites exceeded the confining pressure and resulted in the fracturing of host rocks and expulsion of a Cl- and H2O-rich fluid and residual melt that subsequently formed amphibole veins.The zoned pegmatites of the mafic-ultramafic Hamn intrusion are internally differentiated in terms of grain size, texture, and mineral composition. A characteristic comb-like diopside layering shows a change from numerous small to fewer larger grains from the rim towards the core of the pegmatite pocket. This textural change suggests that the pegmatite-forming melt experienced a transition from a high nucleation rate (N) vs. growth rate (G) ratio to a low ...